Monetary policy in Western Balkan countries and its impact on the economy - Gruikj, Vesna; Brůna, Karel, 1973-; Gevorgyan, Kristine; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
The thesis focuses on analyzing the monetary policy in the Western Balkan countries, and how the monetary policy impacts the economy in the particular country through its monetary policy instruments. The countries being observed are: Albania, Bosnia and Herzegovina, Croatia, Macedonia, and Serbia.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses